Creativity of IPS teachers in growing students' interest in reading using images in Madrasah Ibtidaiyah Al-Islamiah Bangkar Muara Uya - Widari, Amalia; Syarifuddin, Syarifuddin; Mohamed, Rosmah (Komunitas Penulis Ilmiah Nusantara (KaPIN), 2022)
This study aims to explain what are the forms of teacher creativity in fostering reading interest in class students 1A using image media. The use of images here as a tool or media is expected to foster student interest in reading. This research was conducted in Madrasah Ibtidaiyah Al-Islamiyah Bangkar Muara Uya. The subject in this study is the homeroom teacher 1A in MI Al-Islamiyah Bangkar Muara Uya. This research is a field research using qualitative methods. Data were collected through observation, interviews and documentation. The results of this study indicate that the homeroom teacher's creativity 1A in MI Islamiyah Bangkar Muara Uyain fostering students' reading interest consists of: 1) the use of creative learning media such as pictures, pictures of vowels, videos, and other media adapted to the learning material, 2) the use of varied and creative teaching strategies such as discussions, lectures, question and answer , and assignments, 3) creative classroom management such as the formation of the letter "U".